Rancang Bangun Aplikasi Penjualan Online Pada CV. Abilindo Mitra Sejahtera - Salay, Yudiyanto; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract:CV. Abilindo Mitra Sejahtera is importer company of children supplies like clothes, shoes, socks, bags, accessories. Problems faced by CV. Abilindo Mitra Sejahtera is when personal facebook page reaches 5000 friendship, personal page automatically changes to the page, or more recognized with fanspage, resulting in the loss of all photo products. Each post, not all friends on friendlist can see it. To be seen by everyone must use special features provided by facebook. Also in terms of sales note sales are often lost, resulting in a revenue calculation results become incompatible with the truth. To handle these problems, then the application of online sales is created. With the features of the sales are product catalogs, shopping carts, sales reports.The result of tryouts showed that sales application have been made can do register member, receipt of the goods transactions, selling transactions, payment, goods shipping and can inform daily sales report, monthly sales report, annual sales report, invoice sales, payment list and sent list  with the purpose of providing information that can help sales CV . Abilindo Mitra Sejahtera.Keywords: Online shop, web based sales